Quality Assessment of High-FAME Biosolar Fuels (B40–B60) Based on Indonesian Fuel Standards - Muhammad Hasib Nurulloh; Ananda Arif Fradana; Nur Aini; Muhammad Asnari (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2026)
The increasing utilization of biosolar fuels with high FAME (Fatty Acid Methyl Ester) content requires systematic quality evaluation to ensure compliance with fuel quality standards. This study evaluated biosolar fuels with different FAME fractions (B0, B40, B50, B60, and B100), with B40–B60 representing the main blending range and B0 and B100 serving as reference fuels. Fuel quality was assessed based on color, density, flash point, cetane number, distillation characteristics, total acid number (TAN), sulfur content, and water content, with reference to the Indonesian B40 diesel fuel specification under the Cetane Number 48 (CN 48) category as stipulated in Kepdirjen No. 384.K/MG.06/DJM/2024. The results showed that increasing FAME concentration produced a lighter fuel color and increased density from 839.7 kg m−3 (B0) to 876.5 kg m−3 (B100). Flash point increased from 55.6°C (B0) to 80.0°C (B100), while cetane number increased from 47.1 (B0) to 54.9 (B60), indicating improved fuel safety and ignition quality. Distillation temperatures increased with increasing FAME fraction due to the lower volatility of biodiesel components. The Total Acid Number increased from 0.09252 to 0.27320 mg KOH g−1, whereas sulfur content decreased from 0.06622 to 0.00492 % (m/m), reflecting the inherently low sulfur composition of biodiesel. Water content increased substantially from 153.664 mg kg−1 (B0) to 901.970 mg kg−1 (B100) due to the hygroscopic nature of FAME. Activated zeolite treatment, applied at a dosage of 6 g per 500 mL fuel based on preliminary laboratory practice and adsorption conditions applied during the experimental design, reduced water content by approximately 9–24%; however, several blends remained above the allowable limit of 380 mg kg−1. The relatively low flash point observed for B100 may indicate the presence of residual light components originating from production or handling processes and should therefore be interpreted as a limitation of the tested sample rather than a general biodiesel characteristic. These findings indicate that while biodiesel blending improves several fuel properties, effective moisture control remains essential for maintaining the quality and stability of high-FAME biosolar fuels.